The Effects of Game Simulation Implementation on Economics Concept Understanding - Mutiya Oktariani,; Damayanti,; Candra A. Wahyudhi, (Technium Social Sciences Journal, 2023)
Education in the 21st century integrates literacy skill, knowledge, life skills, attitudes and mastery of ICT. These skills can be developed by using learning methods, one of which is game simulation. This study was intended to analyze whether game simulation methods can improve students' conceptual understanding. This study employed a quasi-experimental with non-equivalent control group design. The samples were selected using a purposive sampling method. In this study, class X.IPS.1 was obtained to be the experimental group with a total of 30 people. The data were collected by using tests. Then, they were processed by using SPSS Version 25 software. The result indicated that the hypothesis testing was accepted which implied that there were differences in students’ ability to understand Economics concepts after using the game simulation method. It was concluded that there were differences in students' conceptual understanding abilities before and after using the game simulation method. Therefore, this study was expected to be used as an alternative for Economics learning to construct a more meaningful atmosphere for students.